2015
DOI: 10.1007/s12011-015-0501-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trace Element Concentrations in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a condition that is associated with oxidative stress. Serum trace elements and their related transport proteins, e.g., albumin and ceruloplasmin, play an important role in the antioxidant defense. Trace element status may therefore be involved in the pathogenesis of RA or be affected by the disease activity of this chronic inflammatory condition. The study participants were 110 patients with RA and 100 sex- and age-matched healthy volunteers. Serum concentrations of albumin, cerulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 49 publications
2
26
0
4
Order By: Relevance
“…So the decrease in serum albumin level obtained in the present study could be explained by either that albumin is one of the negative acute phase proteins that decreased after inflammations or due to its activity as antioxidant or both , as shown in the Fig. (2) The results obtained in the present study agree with [25] [26]. Serum Total bilirubin levels is significant decrease in compare to control group, as shown in the Fig.…”
Section: Ra Patient Group N=80 Control Group N=30 P Valuesupporting
confidence: 88%
“…So the decrease in serum albumin level obtained in the present study could be explained by either that albumin is one of the negative acute phase proteins that decreased after inflammations or due to its activity as antioxidant or both , as shown in the Fig. (2) The results obtained in the present study agree with [25] [26]. Serum Total bilirubin levels is significant decrease in compare to control group, as shown in the Fig.…”
Section: Ra Patient Group N=80 Control Group N=30 P Valuesupporting
confidence: 88%
“…Derived neutrophil to lymphocyte ratio (dNLR) was defined as the neutrophil count to (leukocyte–neutrophil count) . Several evidences have demonstrated that systemic inflammation and malnutrition might be associated with disease activity of RA patients and might contribute to the pathogenesis and progression of RA . Circulating immune cells such as lymphocytes, neutrophils, and monocytes can reflect the severity of systematic inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…3 Several evidences have demonstrated that systemic inflammation and malnutrition might be associated with disease activity of RA patients and might contribute to the pathogenesis and progression of RA. 4,5 Circulating immune cells such as lymphocytes, neutrophils, and monocytes can reflect the severity of systematic inflammation. 6 Albumin is a routine marker reflecting both nutritional status and systemic inflammation, while the synthesis of albumin can be suppressed by systematic inflammation and malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…При всех изученных заболеваниях суставов установлены нарушения микроэлементного состава крови, которые участвуют в патогенетических механизмах артритов и определяют их клиническое течение. Микроэлементоз рассматривается как одно из важных клинико-патогенетических составляющих дегенеративно-воспалительных болезней суставов [6,11,17].…”
Section: № (23) 2016unclassified